PEER TO PEER LENDING DALAM POJK, PBI DAN FATWA DSN MUI - Wulandari, Fajrina Eka (IAIN Tulungagung, 2018)
This article discussed about regulation in peer to peer lending of financial technology (fintech). The method used in this article is library research because the case is the latest case. Regulation about transaction in fintech based on, regulation of OJK, regulation of Indonesian Bank and guidance of MUI. Three regulation give the rule for transaction in financial technology to avoid some loss when doing the transaction with other people.Keywords: Fintech, Regulation of OJK, Regulation of Indonesian Bank, Guidance of MUI